Stability of motion of nonlinear systems with fuzzy characteristics of parameters - Martynyuk, A. A.; Martynyuk-Chernienko, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the stability of a stationary solution of a fuzzy dynamical system by a generalized Lyapunov direct method.